(untitled) (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2014)
The article aims to rethink the several stereotypes of Romantic tradition, which are still reproduced in regard to Benvenuto Cellini and his Vita. Using the approaches of intellectual history and iconographical studies, the present study pays attention to the coherent system of lay, scientific and ‘secret’ knowledge of the epoch lurking under the surface of the simplicity and even naivety of the author’s language. I argue that this autobiographical writing embodies a certain type of culture of the self deeply rooted in contemporary medical, alchemical and magical contexts. Organized around the concept of “getting pleasure,” Cellini’s practices of the self are built into the Neo-Platonic picture of the world. Analyzing the two passages of Vita, I demonstrate the author’s spiritual ascent from the corporeal suffering to union with ‘the One’ by means of individual and collective magic rituals, transforming his Life into a work of art.